Analisis Isi Hype Culture dalam Marketing dan Branding Sneakers Lokal Indonesia Analisis Brand Sepatu Compass di Instagram - Putra, Aljannata; Rahmawati, Aulia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explores the phenomenon of hype culture in the marketing and branding practices of local Indonesian brands through a case study of the Instagram account @sepatucompass. Sepatu Compass was selected as the research object due to its success in building an exclusive brand image, strong community engagement, and consumer loyalty through effective digital communication strategies. The study aims to analyze how elements of hype culture such as product scarcity, limited releases, local narratives, and creative collaborations are constructed through digital content to shape brand perception. This research employs a descriptive qualitative approach using content analysis of 92 feed posts, 29 reels, and 11 active highlights published between April 2024 and March 2025. The findings show that Compass consistently utilizes visual narratives, strategic collaborations, and educational and community-based content to create symbolic value and foster emotional engagement with its audience. Instagram proves to be an effective medium for building hype, cultivating collective identity, and strengthening the digital ecosystem between the brand and its community. This study contributes to digital communication studies, local brand strategy development, and understanding consumer culture among youth in the social media era.